Selección de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia de Eloy Alfaro. - Quituisaca Estrada, Thalia Michelle (2023)
The objective of this research is animals selection based on economic characteristics importance in the production of bovine milk at Eloy Alfaro parish. For this, a data collection of each animal owned by the producers was carried out, with this it was analyzed and detemined that the sector has a value of 76% of animals of own origin and 24% of external origin, in the gender of the animals it could be seen a total number of 84% females and only 16% males, in the breed is found that Creole predominates with a 67% value of the total number, In addition, an ant mastitis test (CMT) was performed, which showed mastitis presence at a value of 12% at sector, the milk density was also evaluated, determining that there is milk of excellent quality with a value of 32.75 g/ml and finally the daily weight gain was analyzed, determining that the animals have a low gain ranging between 200 and 280 g/day due to lack nutrients at feed. Another factor was hardiness because these animals, despite living in unfavorable conditions still producing, hence the need for a genetic improvement program in the area in order to contribute with animals to adapt to the productive conditions and environmental systems of the country. It is concluded that the animals begin to improve the production and profitability of dairy farms.